Medina dalam Pendidikan Modern: Kepemimpinan Nabi sebagai Kerangka Kerja untuk Tata Kelola Pendidikan yang Inklusif dan Transformatif - Faqih Jalaludin Muhammad; Imelia Sahda Salsabilla (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
This research aims to examine in depth the life history of the Prophet Muhammad SAW during the Medina period, as well as explore its relevance in the context of leadership and education today. The main issue studied is how the transformation of the Prophet's da'wah in Medina formed the foundation of a strong Islamic socio-political system, and how its values can be applied in the modern world of education. An important context of this issue is the lack of research that explicitly links the prophetic values of the Medina period with contemporary educational leadership. This research uses the library research method by examining primary sources such as Sirah Nabawiyah and other academic literature. The results of the study show that the Prophet's principles such as social justice, cross-group brotherhood, interfaith tolerance, and leadership regeneration are very relevant to build an inclusive, collaborative, and civilized education system. The conclusion of this study confirms that the Prophet's leadership in Medina is a transformative model that can be used as an example in managing educational institutions in the modern era. It is recommended that follow-up research be carried out with a field approach to test the implementation of these values in real practice